EUROPEAN COMPANIES: EVALUATION FOR SHARIA COMPLIANCE “OPPORTUNITIES AND CHALLENGES” - Biancone, Paolo Pietro; Radwan, Maha (European Journal of Islamic Finance, 2016)
The continuous growth of Islamic finance investments and the innovation in its various financial instruments make it an attractive financial system especially for the Western countries. Islamic finance is currently introduced in some European countries however the rest of the continent is studying the idea of having dual financial system (i.e. Islamic system and conventional system). Attracting Islamic investors to Europe requires the compatibility of the investments with Sharia. The aim of this paper is to evaluate European companies for being Sharia compliant. Qualitative and empirical approaches are used in the research methodology to test the European companies’ eligibility using a Sharia compliant methodology screening. The results should be a key element in understanding the nature of those companies and figuring out if it will be a win -win situation; in one hand those companies can be financed through Islamic financial instruments and on the other hand examine the profitability of those companies.